The formation of certain course concepts of ancient history in fifth grade - Vaitkevičius, J. (Psichologija, 1965)
One of the most important tasks assigned to a Soviet school is scientific outlook formation. The basis of this outlook is knowledge of our environment and patterns of social life. These patterns are revealed to a person only upon mastering deep and solid knowledge of patterns. Thus, each subject in school must provide sufficient knowledge. We analyzed the quality and quantity of fifth grade students’ knowledge about ancient history. It turned out that knowledge is soon forgotten and sometimes even distorted over time. This, of course, complicates learning about the evolution of society, the emergence of classes, the formation of states, etc. The cause of forgetfulness, first of all, is the structure of the curriculum, textbooks, and teaching aids. Textbooks are stuffed with knowledge, so-called knowledge elements; besides, even though all the facts are closely linked, they are presented individually, without a system, in isolation. Curricula and teaching aids also do not form systematic knowledge for students. Therefore, teachers frequently give themselves the objective of merely providing new knowledge and do not base it on the old. As a result, a systematic scientific worldview does not form, and students retain merely the breadcrumbs of knowledge. Formerly acquired knowledge becomes soon forgotten when not included in an overall analysis.